GATR-3, a Peptide That Eradicates Preformed Biofilms of Multidrug-Resistant Acinetobacter baumannii - Monique L. van Hoek; Fahad M. Alsaab; Ashley M. Carpenter (MDPI AG, 2023)
Acinetobacter baumannii is a gram-negative bacterium that causes hospital-acquired and opportunistic infections, resulting in pneumonia, sepsis, and severe wound infections that can be difficult to treat due to antimicrobial resistance and the formation of biofilms. There is an urgent need to develop novel antimicrobials to tackle the rapid increase in antimicrobial resistance, and antimicrobial peptides (AMPs) represent an additional class of potential agents with direct antimicrobial and/or host-defense activating activities. In this study, we present GATR-3, a synthetic, designed AMP that was modified from a cryptic peptide discovered in American alligator, as our lead peptide to target multidrug-resistant (MDR) A. baumannii. Antimicrobial susceptibility testing and antibiofilm assays were performed to assess GATR-3 against a panel of 8 MDR A. baumannii strains, including AB5075 and some clinical strains. The GATR-3 mechanism of action was determined to be via loss of membrane integrity as measured by DiSC3(5) and ethidium bromide assays. GATR-3 exhibited potent antimicrobial activity against all tested multidrug-resistant A. baumannii strains with rapid killing. Biofilms are difficult to treat and eradicate. Excitingly, GATR-3 inhibited biofilm formation and, more importantly, eradicated preformed biofilms of MDR A. baumannii AB5075, as evidenced by MBEC assays and scanning electron micrographs. GATR3 did not induce resistance in MDR A. baumannii, unlike colistin. Additionally, the toxicity of GATR-3 was evaluated using human red blood cells, HepG2 cells, and waxworms using hemolysis and MTT assays. GATR-3 demonstrated little to no cytotoxicity against HepG2 and red blood cells, even at 100 μg/mL. GATR-3 injection showed little toxicity in the waxworm model, resulting in a 90% survival rate. The therapeutic index of GATR-3 was estimated (based on the HC50/MIC against human RBCs) to be 1250. Overall, GATR-3 is a promising candidate to advance to preclinical testing to potentially treat MDR A. baumannii infections.